PENGARUH LOSS AVERSION DAN OVERCONFIDENCE TERHADAP INVESTMENT PERFORMANCE DENGAN INVESTMENT EXPERIENCE SEBAGAI VARIABEL MODERASI PADA INVESTOR GALERI INVESTASI DI SURABAYA - Novi Amelia; Rahman Amrullah Suwaidi; Fani Khoirotunnisa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Public participation in investment, especially within the banking sector, is witnessing notable growth driven by technological advancements and increased access to information. Nonetheless, this growth masks a reality where investor behaviour is often irrational and influenced by psychological factors. Insights from behavioural finance reveal that investment decisions rely on objective analysis, emotional factors, and individual perceptions. Specifically, loss aversion and overconfidence biases are thought to affect investment performance. Additionally, investment experience can amplify or diminish the impact of investment outcomes. This study identifies and analyses how loss aversion and overconfidence influence investment performance, with investment experience as a moderating variable. Employing a quantitative methodology, the research used purposive sampling to distribute a questionnaire at the Surabaya Investment Gallery. Data analysis was conducted through the Partial Least Square (PLS) method, utilizing SmartPLS 3.0. The study’s findings reveal that: 1) Loss aversion significantly positively impacts investment performance among investors at the Surabaya Investment Gallery; 2) Overconfidence also has a significant positive effect on investment performance among these investors; 3) Investment experience moderates the effect of loss aversion on performance; and 4) Investment experience similarly moderates the effect of overconfidence on performance among investors at the Surabaya Investment Gallery. These findings elevate behavioural finance literature and can guide investors toward making more rational decisions.